2018
DOI: 10.4103/jios.jios_167_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reliability and Validity of Posteroanterior Cephalometric Measurements Obtained from AutoCEPH© and Dolphin® Cephalometric Software Programs with Manual Tracing

Abstract: The objective of this study is to evaluate the reliability and accuracy of linear and angular cephalometric measurements obtained from two computerized cephalometric analysis software programs, namely AutoCEPH © (version 2.1.1) and Dolphin ® (version 11.9) as compared to manual tracings in posteroanterior (PA) cephalometry. Materials and Methods: Sixty pretreatment (PA) cephalograms were selected from the database of a postgraduate orthodontic clinic. The digital images of each cephalogram were imported direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(28 reference statements)
3
1
0
1
Order By: Relevance
“…When predicted and actual post-treatment values of interincisal angle, U1-SN, U1-NA (mm), U1-NA (deg), LI-NB (mm), LI-NB (deg), U1-PP (deg), and IMPA were compared, it was found that significant difference was found for all the parameters except UI-SN and UI-PP showing that the software prediction was accurate for changes occurring in only these two parameters. Similar results were found in the study done by Izabella, 22 Thomas, 23 and Lew. 18…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When predicted and actual post-treatment values of interincisal angle, U1-SN, U1-NA (mm), U1-NA (deg), LI-NB (mm), LI-NB (deg), U1-PP (deg), and IMPA were compared, it was found that significant difference was found for all the parameters except UI-SN and UI-PP showing that the software prediction was accurate for changes occurring in only these two parameters. Similar results were found in the study done by Izabella, 22 Thomas, 23 and Lew. 18…”
Section: Discussionsupporting
confidence: 91%
“…When predicted and actual post-treatment values of interincisal angle, U1-SN, U1-NA (mm), U1-NA (deg), LI-NB (mm), LI-NB (deg), U1-PP (deg), and IMPA were compared, it was found that significant difference was found for all the parameters except UI-SN and UI-PP showing that the software prediction was accurate for changes occurring in only these two parameters. Similar results were found in the study done by Izabella, 22 Thomas, 23 and Lew. 18 The inaccuracy in prediction of incisor inclination might be attributed to the difficulty faced during placement of the tooth while using treatment simulation module in the software or due to failure of the clinician to attain the desired objective.…”
Section: Meansupporting
confidence: 91%
“…When manual tracing and AutoCeph® groups were compared, most of the parameters (Table 3) showed a positive agreement, which shows that AutoCeph® can be used instead of manual tracing, as it is user-friendly, time saving, and makes work easier, which is similar to the study by Sangroula et al 13 The results of this study when comparing manual method with the NemoCeph® (Table 3) cephalometric tracing showed a similar conclusion as that reported by Francisco et al 23 The results showed that NemoCeph® may be used with reliability to make cephalometric measurements. There is no significant difference between the manual and Nemoceph® for most of the linear and angular cephalometric parameters.…”
Section: And Khader Et Al19 (Table 2)supporting
confidence: 80%
“…Many studies have examined the performance of commercially available software and mobile apps used for cephalometric analysis. 13 Mobile applications have the potential to advance dentistry. Orthodontic clinicians and patients have employed a variety of smartphone apps relevant to orthodontics.…”
Section: Discussionmentioning
confidence: 99%
“…Lalakiya y col. 5 compararon el trazado manual con el digital mediante el uso del software FACAD cuyos resultados mostraron diferencia significativa en seis de dieciocho medidas analizadas, siendo ellas el ángulo facial, ángulo oclusal -SN, inclinación del plano oclusal, ángulo Go -Gn a SN, plano Ar -Go y el ángulo interincisal, siendo ese último un resultado similar a este estudio. Sangroula y col., 16 evaluaron la confiabilidad y precisión de mediciones cefalométricas lineales y angulares comparando los programas AutoCEPH y Dolphin con el método de rastreo manual, en 17 parámetros cefalométricos. Para ello, evaluaron el CCI con un resultado de 0,813-0,998 en todos los parámetros al comparar los tres métodos.…”
Section: Discussionunclassified